(untitled) (Bangladesh Journal of Livestock Research, 2020)
Buffalo is a highly potential animal species in terms of milk and meat production but traditionally they are regarded as poor breeder. In vitro embryos production technology has been introduced in many countries to improve reproductive efficiency of buffalo. Considering the above fact, the present study was undertaken aiming to produce in vitro buffalo embryo in the laboratory. Ovaries of slaughtered buffaloes were collected from abattoir and transported to the laboratory within 4 to 5 hr of slaughter. Cumulusoocyte- complexes (COCs) possessing an even cytoplasm and covered with minimum 3 layers of compact cumulus cells was selected for in vitro maturation (IVM) for 24 hr (5% CO2 in air at 38.5°C with maximum humidity). After IVM, the presumptive matured COCs were co-cultured with capacitated fresh spermatozoa for 18 hr After IVF, the presumptive zygote were denuded, washed and transferred in to in vitro culture medium (IVC 1) for 3 days. After three days cleavage were recorded and 4 cell embryos were transferred in to in vitro culture media II for next 2 days. The development of embryos was evaluated on day 6. A total of 227 buffalo ovaries were collected from the slaughterhouse and categorized into 2 groups based on presence (n=83) or absence (n=144) of corpus luteum (CL). A total of 1464 follicles were counted on the ovarian surface, 1066 being from CL absent and 398 from CL-containing ovaries. A significantly higher (P<0.01) number of follicles, aspirated follicles, normal COCs and total COCs (7.4 ± 0.21, 5 ± 0.00, 1.98 ± 0.77 and 2.98 ± 0.16 respectively) were observed in CL-absent ovaries than those aspirated from CL-containing ovaries (4.80 ± 0.17, 3.92 ± 0.95, 0.88 ± 0.60 and 1.88 ± 0.16 respectively). Total 358 normal COCs were set for in vitro maturation and underwent for IVF and IVC. Results showed that cleavage rates were 56.42%. Among the cleaved embryos, 137 were at 2-cell stage and 65 were at 4-cell stage. Therefore, development rate to 2 cell and 4-cell stage was 38.27% and 18.15% respectively. No embryo developed beyond 4-cell stage. This result indicates that follicle and oocyte numbers and oocyte quality are associated with CL of ovaries and current culture system support in vitro embryo production upto 4-cell stage. The in vitro culture condition may be improved for increasing efficiency of embryo production. Bangladesh J. of Livestock Res. 21-25: 127-132, 2018